gem-dialkyl effect in diphosphine Ligands: synthesis, coordination behavior, and application in Pd-catalyzed hydroformylation - Tay,DWP; Nobbs,JD; Romain,C; White,AJP; Aitipamula,S; van,Meurs M; Britovsek,GJP (ACS Catalysis, 2020)
A series of palladium complexes with C3-bridged bidentate bis(diphenylphosphino)propane ligands with substituents of varying steric bulk at the central carbon have been synthesized. The size of the gem-dialkyl substituents affects the C–C–C bond angles within the ligands and consequently the P–M–P ligand bite angles. A combination of solid-state X-ray diffraction (XRD) and density functional theory (DFT) studies has shown that an increase in substituent size results in a distortion of the 6-membered metal–ligand chair conformation toward a boat conformation, to avoid bond angle strain. The influence of the gem-dialkyl effect on the catalytic performance of the complexes in palladium-catalyzed hydroformylation of 1-octene has been investigated. While hydroformylation activity to nonanal decreases with increasing size of the gem-dialkyl substituents, a change in chemoselectivity toward nonanol via reductive hydroformylation is observed.